Bed topography of Princess Elizabeth Land in East Antarctica - Cui, X; Jeofry, H; Greenbaum, JS; Guo, J; Li, L; Lindzey, LE; Habbal, FA; Wei, W; Young, DA; Ross, N; Morlighem, M; Jong, LM; et al. (Earth System Science Data, 2020)
We present a topographic digital elevation model (DEM) for PrincessElizabeth Land (PEL), East Antarctica. The DEM covers an area of ∼900 000 km 2 and was built from radio-echosounding data collected during four campaigns since 2015. Previously, togenerate the Bedmap2 topographic product, PEL's bed was characterized fromlow-resolution satellite gravity data across an otherwise large( >200 km wide) data-free zone. We use the mass conservation (MC)method to produce an ice thickness grid across faster flowing ( >30 m yr −1 ) regions of the ice sheet and streamline diffusion in slower flowing areas. The resulting ice thickness model is integrated with an ice surface model to build the bed DEM. Together with BedMachineAntarctica and Bedmap2, this new bed DEM completes the first-ordermeasurement of subglacial continental Antarctica an international mission that began around 70years ago. The ice thickness data and bed DEMs of PEL (resolved horizontally at 500 m relative to ice surface elevations obtained from the Reference Elevation Model of Antarctica REMA) are accessible from https://doi.org/10.5281/zenodo.4023343 (Cui et al., 2020a) and https://doi.org/10.5281/zenodo.4023393 (Cui et al., 2020b).